Optimal supervisory architecture and financial integration in a banking union - Jean-Edouard Colliard (European Central Bank (ECB), 2015)
Both in the United States and in the Euro area, bank supervision is the joint responsibility of local and central/federal supervisors. I study how such a system can optimally balance the lower inspection costs of local supervisors with the ability of the central level to internalize cross-border or interstate externalities. The model predicts that centralised supervision endogenously increases market integration and cross-border externalities, further strengthening the need for centralised supervision. This complementarity implies that, for some parameterizations of the model, the economy can be trapped in a local supervision equilibrium with low supervision and integration. In such a case, the forward-looking introduction of a centralized supervisory architecture achieves a superior equilibrium.
Keywords: D53; G21; G28; G33; G38; L51; 330; bank supervision; banking union; Financial integration; regulatory federalism; single supervisory mechanism